Twelve tips for postgraduate or undergraduate medics building a basic microsurgery simulation training course. (1st September 2016) - Mason, Katrina A.; Theodorakopoulou, Evgenia; Pafitanis, Georgios; Ghanem, Ali M.; Myers, Simon R.
Abstract: Microsurgery is used in a variety of surgical specialties, including Plastic Surgery, Maxillofacial Surgery, Ophthalmic Surgery, Otolaryngology and Neurosurgery. It is considered one of the most technically challenging fields of surgery. Microsurgical skills demand fine, precise and controlled movements, and microsurgical skill acquisition has a steep initial learning curve. Microsurgical simulation provides a safe environment for skill acquisition before operating clinically. The traditional starting point for anyone wanting to pursue microsurgery is a basic simulation training course. We present twelve tips for postgraduate and undergraduate medics on how to set up and run a basic ex-vivo microsurgery simulation training course suitable for their peers.